Innovations, difficulties, and constraints in the manufacturing of jaggery and jaggery manufacturing plants - Ukey, P D; Ingale, V M; Yenge, G B; Prathapan, K; Ghatge, J S; Patil, S B; Khot, J A (Journal of Postharvest Technology, 2022)
In India, jaggery is a popular traditional sweetener. It is produced by continuously heating and condensing clear sugarcane juice without the use of chemicals. Currently, people are highly conscious of the health risks associated with eating and place greater importance on food quality. Jaggery is enriched with numerous nutrients, including vitamins, minerals, and protein. Jaggery offers various health benefits such as blood purification, digestion regulation, beauty treatment, improved metabolism, prevention of respiratory issues, and more. The process of making jaggery involves constant heat and mass transfer, transforming fresh sugarcane juice into a concentrated product. The entire process includes various steps, from sugarcane harvesting to shaping the finished product into different sizes and forms depending on its intended use. The unit operations of jaggery processing include juice extraction, juice clarification, boiling to concentrate juice, cooling concentrated juice, molding/shaping, drying, powdering, packing, and storing. All of these practices, which have several drawbacks and difficulties, are employed in traditional jaggery-making plants. The main problems and challenges that manufacturers face today include the inferior crushing efficiency of the sugarcane crusher, the need for vast open space for bagasse drying, labor-intensive processes, the use of various chemical and natural clarifying agents to produce high-quality jaggery, shortened storage life, high fuel consumption, and poor thermal efficiency. This article addresses the different concerns and problems experienced by manufacturers and presents improvements to the plants and jaggery-making process suggested by researchers.